Recent Insights into Microplastic Pollution and Its Effects on Soil Carbon: A Five-Year Ecosystem Review - Anastasia Vainberg; Evgeny Abakumov; Timur Nizamutdinov (Microplastics, 2025)
The widespread presence of microplastics (MPs) is of growing concern for both the scientific community and the public. Contemporary research increasingly focuses on ecosystem transformation and global climate change. We conducted a literature review, consisting of 46 studies, to investigate the consequences of MPs’ influence on the carbon cycle in different soil types across various ecosystems. MPs can affect the cycling of carbon compounds and other biogenic elements by impacting the soil microbiome, enzyme activity, plant growth, litter decomposition, and more. The majority of authors report increased CO2 and/or CH4 emissions in soils containing MPs. However, some studies demonstrate the opposite or a neutral result, and the outcomes can differ even within a single study depending on the soil type and/or the type, form, and size of the MPs used. Further clarification and development of our understanding regarding the impact of MPs on the carbon cycle across different ecosystems remain crucial, taking into account the inclusion of as wide a variety of MPs as possible in future research.